Method verifying the correctness of code refactoring program - Luo, Ting; Guo, Yuan-Bo; Hao, Yao-Hui; Li, Hu (Tongxin Xuebao, 2011)
The program after code refactoring, probably because a number of coding errors were introduced in the process of reconstruction, and could not properly achieve the function of origi-nal program, and therefore it was necessary to verify its correctness. But currently, it's difficult to prove the correctness of program directly; the view of transforming the verification of program correctness into the verification of program equivalence, and proposed a theorem proving technology based on synthesis method to verify the equivalence. The technology could not only avoid the difficulties by directly verifying the correctness of the program, but also could make full use of existing theorem proving tools to improve the level of automation, reducing the difficulty of proof. the principle of the method was presented, the basic assumption and proving environment, and then sum up the key strategies for the formal specification. Finally the equivalence of RC4 algorithm was verified with the presented method, and the experi